Clinical Factors and Cellular Responses of In Situ Human Alveolar Bone–Derived Mesenchymal Stromal Cells Associated With Early Periimplant Marginal Bone Loss: A Prospective Cohort Pilot Study. Issue 5 (October 2019) - Kim, Dong-Jun; Kim, Seul-Ki; Cha, Jae-Kook; Lee, Jung-Seok; Kim, Chang-Sung
Abstract : Purpose: To investigate clinical factors and cellular responses of in situ human alveolar bone–derived mesenchymal stromal cells involved in early periimplant marginal bone loss. Materials and Methods: Thirty-seven completely or partially edentulous patients were enrolled in this study. Periapical radiographs were taken at the time of implant surgery, at 3-month follow-up, and at 1-year follow-up. Univariate analysis and multiple logistic regression were performed to investigate the associations between marginal bone loss and study variables. The mRNA expression levels of 21 bone-remodeling– and tissue-healing–associated genes were analyzed by subgroup. Results: Thirty-one patients with 98 implants were followed. The incidence and mean amount of bone loss were higher for overdentures than for other prosthesis and higher for the maxilla than for the mandible. The bone loss group showed lower mRNA expression levels of runt-related transcription factor-2, bone morphogenetic protein-2, and peroxisome proliferator–activated receptor gamma-2 and higher receptor activator of NKκB ligand/osteoprotegerin (RANKL/OPG) ratio. Conclusion: Within the limitations of the study, certain genes involved in bone remodeling (runt-related transcription factor-2 [Runx-2], bone morphogenetic protein-2 [BMP-2], and peroxisome proliferator–activated receptor gamma-2 [PPARγ-2]) and RANKL/OPG are correlated with early periimplant bone loss, with the type of suprastructure and the involved jaw being significant clinical factors. Abstract : Supplemental Digital Content is Available in the Text.